Evaluating Research Trends and Gaps in Disaster Literacy within Science Education: A Bibliometric Perspective - Prasetyaningsih Prasetyaningsih; Ida Kaniawati; Lala Septem Riza; Judhistira Aria Utama (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate research trends, gaps, and global patterns in disaster literacy within science education to identify areas for improvement and provide actionable recommendations for enhancing education strategies in disaster-prone regions. Methodology: A bibliometric analysis was conducted using data from the Scopus database (2000-2024). Tools used include R Studio with the Bibliometrix package for generating visualizations such as co-occurrence networks, word clouds, and trend analyses. The dataset comprises 315 articles selected using “disaster literacy” and